2023
DOI: 10.1371/journal.pone.0268385
|View full text |Cite
|
Sign up to set email alerts
|

New insights from short and long reads sequencing to explore cytochrome b variants in Plasmopara viticola populations collected from vineyards and related to resistance to complex III inhibitors

Abstract: Downy mildew is caused by Plasmopara viticola, an obligate oomycete plant pathogen, a devasting disease of grapevine. To protect plants from the disease, complex III inhibitors are among the fungicides widely used. They specifically target the mitochondrial cytochrome b (cytb) of the pathogen to block cellular respiration mechanisms. In the French vineyard, P. viticola has developed resistance against a first group of these fungicides, the Quinone outside Inhibitors (QoI), with a single amino acid substitution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In both cases, the electron transfer process is blocked, leading to the inhibition of mitochondrial respiration [4446]. Indeed, the quinone inside inhibitors used in agriculture are highly specific against oomycete pathogens [47,48]. Furthermore, it has previously been demonstrated that P. infestans mitochondria exhibit sensitivity to cyanide, a known inhibitor of C c O activity in yeast cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the electron transfer process is blocked, leading to the inhibition of mitochondrial respiration [4446]. Indeed, the quinone inside inhibitors used in agriculture are highly specific against oomycete pathogens [47,48]. Furthermore, it has previously been demonstrated that P. infestans mitochondria exhibit sensitivity to cyanide, a known inhibitor of C c O activity in yeast cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ONT sequencing was used alongside pyrosequencing, qPCR, Ion Torrent, and Illumina sequencing to profile cytochrome b in single spored isolates and field populations of Plasmopara viticola, a pathogen of grapes 33 . The use of multiple technologies alongside biological assays allowed the authors to produce a comparative analysis highlighting the advantages and limitations of each.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multiple technologies alongside biological assays allowed the authors to produce a comparative analysis highlighting the advantages and limitations of each. Unlike other sequencing technologies, ONT sequencing detected multiple SNPs in one gene from mixed field samples; however, the main drawback was sequencing errors 33 . The ONT assay had a sensitivity limit of 5% based on detection of unexpected variants 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations